Necrotizing Soft Tissue Infections in Intravenous Drug Users: A Vascular Surgical Emergency. Issue 5 (May 2015) - Mittapalli, D.; Velineni, R.; Rae, N.; Howd, A.; Suttie, S.A.; ,
Abstract : Objective: To assess the short and long-term outcomes of necrotizing soft tissue infection (NSTI) in intravenous drug users (IVDU) in a regional vascular centre. Methods: This was a retrospective analysis of all IVDUs with NSTI admitted to the regional vascular surgical unit between January 2009 and July 2014. Clinical outcome measures were interval between admission and surgery, length of ITU/HDU and hospital stays, post-operative complications, in hospital and one year mortality. Results: 25 patients were admitted. The median age was 39 years (range 30–53 years) with a female to male ratio of 1:3.3. The median interval between admission and surgery was 23 hours (range 2–195 hours), however, this was significantly less when the admitting specialty was directly to vascular surgery (median 4 hours, range 2–7) compared with other specialties (median 38 hours, range 7–195 hours). Ten patients required HDU/ITU care with a median duration of 4 days (range 1–12 days). Five patients (20%) required amputation, of whom two (40%) had a prosthetic limb fitted. There was one in hospital death (4%). Another patient died while awaiting limb fitting 4 months post discharge, giving a 1 year mortality of 8%. Conclusions: NSTI in IVDUs carries high risk of amputation with a very low rate of limb fitting. Intervention is significantly delayed when the admitting specialty is not vascular surgery, and half of these patients require HDU/ITU care, with significant morbidity and mortality. Early diagnosis and referral to vascular surgery is crucial in management of these patients.